Implementation of Sharia Business Ethics in Indonesian Sharia Banking (Case Study of Bank BJBS KCP Cimahi) - Ryan Renaldi; Muhammad Al Mighwar (Penerbit Hellow Pustaka, 2023)
This articel's goal is to examine and debate the ethical principles that Indonesian Islamic banking practices have adopted as norms, particularly in resolving practical operational issues based on exploratory investigations. Four consumers and three managers of Islamic banks served as the research samples in this study, which was done at Islamic Banking in Cimahi. The analysis's findings suggest three things, all of which are supported by the notion of business ethics: First, Islamic bankers have been successful in forging cordial bonds with stakeholders and customers. Second, they consistently act responsibly while handling difficult situations and uphold high personal moral standards, even in the face of regulatory changes made by the parent bank. These are informal learning opportunities for writers and readers to fulfill their obligations so that they may apply moral principles to organizations. In order to increase the professionalism and operational quality of sharia banking in Indonesia, the author expects that this article will serve as a theoretical and practical resource and guide for regulators and sharia banking practitioners. The results still need to be verified and further generalized because this study's sample size and population coverage are restricted.